The Effect of Implementing the Regional Financial Management Information System (SIMDA) On the Quality of Financial Reports at The Gowa Regency Livestock and Plantation Service - Ninda Pratiwi; Rustan, Rustan; Firman Syah (International Journal of Economic Research and Financial Accounting, 2024)
This research is a type of quantitative research with the aim of finding out the effect of the Implementation of the Regional Financial Management Information System (SIMDA) on the Quality of the Financial Reports of Dinas Peternakan dan Perkebunan Gowa Regency. The population in this study were 30 employees who were at the Gowa Regency Dinas Peternakan dan Perkebunan Office. The sample used is saturated sampling, saturated sampling is a sampling technique when all populations are sampled. The data used in this study is primary data. Primary data is data in the form of information directly obtained from the results of a questionnaire using a Liker scale. The analysis techniques used are validity test, reliability test, simple regression test, T test and R test. The results of the study show data using statistical calculations through the application of Statistical Package for the Social Science (SPSS) version 27 regarding the Effect of Application of Regional Financial Management Information System (SIMDA) on the Quality of Financial Reports of Dinas Peternakan dan Perkebunan Gowa Regency which has been discussed from the previous chapter, the authors draw conclusions namely the Implementation of the Regional Financial Management Information System (SIMDA) has a positive and significant effect on the Quality of the Gowa Regency Dinas Peternakan dan Perkebunan Financial Reports.